Intraperitoneal chemotherapy and cytoreductive surgery for peritoneal metastases coupled with curative treatment of colorectal liver metastases: an updated systematic review. (4th March 2017) - El-Nakeep, Sarah; Rashad, Noha; Oweira, Hani; Schmidt, Jan; Helbling, Daniel; Giryes, Anwar; Petrausch, Ulf; Mehrabi, Arianeb; Decker, Michael; Abdel-Rahman, Omar
ABSTRACT: Introduction : We aimed to assess the efficacy and safety of delivering intraperitoneal chemotherapy and cytoreductive surgery for peritoneal metastases coupled with curative treatment of colorectal liver metastases. Areas covered : A comprehensive literature search using PubMed was conducted to screen for eligible records. Studies evaluating colorectal surgery and intraperitoneal chemotherapy combined with curative treatment of liver metastases were included. We excluded duplicate publications. Sixty-seven full-text papers were assessed and six papers were finally included. The overall survival in the included studies ranged from 6–49 months. Five-year survival ranged from 18%-28%, three-year survival ranged from 22%-42% and two-year survival ranged from 34%-78%. Survival was lower in patients with liver metastases and peritoneal carcinomatosis (PC) than those with PC alone in the majority of studies. Expert commentary : This review poses questions rather than presenting answers. The heterogeneity of survival data suggests the possible benefit of this aggressive treatment approach in selected patients. Standardization of the technique used for intraperitoneal chemotherapy instillation, agent used as well as the systemic chemotherapy and targeted therapy type and duration through prospective controlled trials is required to provide an evidence of a higher strength to support or prohibit this treatment strategy.